Altered Folate Availability Modifies the Molecular Environment of the Human Colorectum: Implications for Colorectal Carcinogenesis - Protiva, Petr; Mason, Joel B.; Liu, Zhenhua; Hopkins, Michael E.; Nelson, Celeste; Marshall, James R.; Lambrecht, Richard W.; Pendyala, Swaroop; Kopelovich, Levy; Kim, Myungjin; Kleinstein, Steven H.; Laird, Peter W.; et al. (Cancer prevention research (Philadelphia, Pa.), 2011)
Low folate status increases colorectal cancer risk. Paradoxically, overly abundant folate supplementation, which is not uncommon in the United States, may increase risk. The mechanisms of these effects are unknown. We conducted two translational studies to define molecular pathways in the human colon altered either by folate supplementation or by dietary folate depletion (followed by repletion). In the first study, 10 healthy, at-risk volunteers (with documented stable/normal folate intake) received supplemental folic acid (1 mg/d) for 8 weeks. In the second study, 10 similar subjects were admitted to a hospital as inpatients for 12 weeks to study folate depletion induced by a low folate diet. A repletion regimen of folic acid (1 mg/d) was provided for the last 4 of these weeks. Both studies included an 8-week run-in period to ensure stabilized folate levels prior to intervention. We obtained 12 rectosigmoid biopsies (from 4 quadrants of normal-appearing mucosa 10–15 cm from the anal verge) at baseline and at measured intervals in both studies for assessing the primary endpoints: genome-wide gene expression, genomic DNA methylation, promoter methylation (depletion/repletion study only), and p53 DNA strand breaks. Serum and rectosigmoid folate concentrations accurately tracked all changes in folate delivery (P < 0.05). In the first study, gene array analysis revealed that supplementation upregulated multiple inflammation- and immune-related pathways in addition to altering several 1-carbon–related enzymes (P < 0.001). In the second study, folate depletion downregulated genes involved in immune response, inflammation, the cell cycle, and mitochondrial/energy pathways; repletion reversed most of these changes. However, changes in gene expression after repletion in the second study (involving immune response and inflammation) did not reach the levels seen after supplementation in the first study. Neither genomic nor promoter-specific DNA methylation changed during the course of the depletion/repletion protocol, and genomic methylation did not change with supplementation in the first study. p53 DNA strand breaks increased with depletion after 12 weeks. In sum, depletion downregulates, whereas repletion or supplementation upregulates pathways related to inflammation and immune response. These findings provide novel support to the concept that excessive folate supplementation might promote colorectal carcinogenesis by enhancing proinflammatory and immune response pathways. These results indicate that modest changes in folate delivery create substantial changes in the molecular milieu of the human colon. Cancer Prev Res; 4(4); 530–43. ©2011 AACR.